2016
DOI: 10.1016/j.optom.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Intraeye retinal nerve fiber layer and macular thickness asymmetry measurements for the discrimination of primary open-angle glaucoma and normal tension glaucoma

Abstract: PurposeThe aim of this study was to evaluate the diagnostic capability of intraeye retinal nerve fiber layer (RNFL) thickness and macular thickness (MT) asymmetry measurements for the discrimination of normal tension glaucoma (NTG) and primary open-angle glaucoma (POAG) using spectral domain optical coherence tomography (SD-OCT).MethodsA total of 90 subjects were enrolled including 30 consecutive healthy subjects, 30 consecutive subjects with POAG, and 30 consecutive subjects with NTG. RNFL thicknesses around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Furthermore, although a decrease in RNFL and macular thicknesses has been reported in glaucomatous eyes, there is a paucity of data on the discriminating capability of these parameters between NTG and POAG. We have previously established normative data on RNFL thickness in our population and also highlighted the relation between RNFL thickness and visual field sensitivity along with the significant potential of intraeye macular thickness asymmetry for the discrimination of NTG and POAG . In this study, we aimed to establish the distinction in these parameters between NTG and POAG to provide a new dimension to the diagnosis and management of these entities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although a decrease in RNFL and macular thicknesses has been reported in glaucomatous eyes, there is a paucity of data on the discriminating capability of these parameters between NTG and POAG. We have previously established normative data on RNFL thickness in our population and also highlighted the relation between RNFL thickness and visual field sensitivity along with the significant potential of intraeye macular thickness asymmetry for the discrimination of NTG and POAG . In this study, we aimed to establish the distinction in these parameters between NTG and POAG to provide a new dimension to the diagnosis and management of these entities.…”
mentioning
confidence: 99%
“…We have previously established normative data on RNFL thickness in our population and also highlighted the relation between RNFL thickness and visual field sensitivity along with the significant potential of intraeye macular thickness asymmetry for the discrimination of NTG and POAG. 16,21,22 In this study, we aimed to establish the distinction in these parameters between NTG and POAG to provide a new dimension to the diagnosis and management of these entities. This could further contribute to early detection, prior to the observance of functional defects on the subjective tests.…”
mentioning
confidence: 99%
“…30 Utility of vertical macular asymmetry for glaucoma detection has been the subject of a number of studies since then. 7,25,72,76,168,186,191,226,227,344,366,386,414,416,418 However, differences in study design including sample size, type of glaucoma, refractive error, ethnicity, disease stage, layer(s) of interest and method of asymmetry analysis should be considered when comparing the results of these studies. Most current SD-OCT devices are able to measure GCC, GCIPL, mRNFL, and FMT that could be used for hemispheric intra-eye or inter-eye asymmetry comparisons.…”
Section: F Alternative Macular Outcome Measures: Vertical Macular Asymmetry and Microcystic Macular Edemamentioning
confidence: 99%
“…Various methods have been used to estimate vertical asymmetry along the temporal raphe or horizontal midline, including thickness difference, 25,76,168,186,191,227,333,335,344,366,386,416 inferior to superior retinal thickness ratio, 30, 186 and the absolute value of the logarithm of superior/inferior retinal thickness. 168,414 Spectralis SD-OCT (Heidelberg Engineering, Germany) was the first OCT device to incorporate a macular asymmetry analysis within its macular imaging algorithm (PPA) (Figure 6).…”
Section: F Alternative Macular Outcome Measures: Vertical Macular Asymmetry and Microcystic Macular Edemamentioning
confidence: 99%
“…4,5 In normal eyes, the retinal layers seem to be fairly symmetric in terms of the mean thickness in the central parafoveal region between the upper and lower segments as determined by SD-OCT. 6 Asymmetrical differences in the thickness of the inner retinal layer between the upper and lower segments of the macula in PPG eyes were initially investigated using SD-OCT in 2011. 7 Since then, several studies have revealed that asymmetry in the thickness of the retinal layers tends to offer better diagnostic performance than assessment of other thickness parameters, [8][9][10][11][12][13][14] and asymmetry in the thickness of the ganglion cell layer (GCL)/inner plexiform layer (IPL) tends to offer better diagnostic performance than in the RNFL layer in glaucomatous or PPG eyes. 15 However, the degree of difference between the values of the upper and lower segments of the macular inner retinal layers that defines abnormal conditions in the clinical diagnosis of PPG remains to be determined.…”
Section: Introductionmentioning
confidence: 99%